Development of Multiple Representation-Based General Chemistry Textbook Using Guided Inquiry - Ifah Silfianah (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
This study aims to describe the development process and determine the feasibility of multiple representation-based textbooks that are designed with a guided inquiry model. The method used in this research is the Research & Development (R&D) with the ADDIE (Analyze, Design, Develop, Implementation, Evaluate) model. Analyze stages are carried out in the form of curriculum analysis, concepts, and learning resources. In the design process, textbooks are made following the guided inquiry learning stages and design the media in the form of images that show multiple representations so that an initial draft is produced. At the Develop stage, draft books are printed and reproduced for validation and revision. The next step of implementation is carried out through a small-scale trial to determine the initial response to the textbook. In the final stage (Evaluation), the textbook on the results of the small-scale trial was revised to be used in the medium-scale trial to get the textbook's final response data. This study involved ten students in the chemical Tadris department in the small group and 29 students in the moderate group. The instrument used was the validation sheet and the language response sheet and the presentation of the textbook.  Data of expert validation and trial results were analyzed descriptively and qualitatively in the form of percentages using a Likert scale. The results showed the feasibility of the content, linguistic, presentation, and graphic textbooks, respectively 95.33%, 94.76%, 92.16%, and 92.58%. The suitability of the textbooks with the guided inquiry syntax and multiple presentations was 98.33% each. A small group trial shows that the language aspect gets 84.33 scores, and the presentation aspect is 84.75. After the textbook was revised, the trial results for the medium group showed that the linguistic aspect value was 90.34, and the presentation aspect was 92.59. Overall it can be concluded that the textbooks developed are very suitable for use in learning.